ROMANIAN TRADE WITH POTATOES IN THE EUROPEAN UNION CONTEXT - Bianca Eugenia SOARE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The scope of this study was to highlight Romania's position within the existing community context, in the period 2011-2016. Thus it is noted that our country obtained only 5.53% of total community production that is 3,123,363.33 t compared to 56,439,851.67 t in the EU, it achieved 0.07% of the value of exports ($ 1,721.17 compared to $ 2,645,692.33 in the EU, its import value accounts for 1.13% of the EU potato import value, that is $ 26461.50 compared to $ 2347447.83. The national trade balance for potatoes is deficient, similar with the European Union situation. Romania can improve its production and international trade results through appropriate measures to support the respective production sector (i.e. potato production).